The impact of economic and supply chain trends on British warehousing - Baker, Peter; Sleeman, Jon (Cranfield University, 2011)
Purpose: Warehouses are key nodes in many supply chains and typically represent over 20% of logistics costs. However, other than property market studies, there has been relatively little research on warehousing, particularly as regards how trends in warehouses may relate to changes in such parameters as wider economic and supply chain factors. The purpose of this paper is to examine this area in order to explore how trends in warehousing may relate to existing warehousing and supply chain theory so as to facilitate further research into the relationship between warehousing and "smarter" logistics strategies and efficient supply chain performance. Research approach: The paper is based on a longitudinal study examining the take-up (i.e. occupation) of new large warehouses in Great Britain over the past 16 years covering some 700 records. For the purposes of this study, large warehouses are classified as those over 100,000 square feet (9,290 square metres) in area. These trends, together with those of total warehouse stock, are then related to national statistics, warehouse surveys, supply chain changes and other relevant data over that period. Findings and Originality: This is a rare longitudinal study of this subject. It is found that, until the recent recession, the total warehouse stock, as well as the take-up of large warehouses, has been increasing and this can be associated with such factors as economic growth, retail spending and globalisation. Both the footprint and height of large warehouses has been rising and this may be due to such factors as network economies and warehouse technology. The locations of warehouses are becoming more dispersed, possibly due to the growth in e-commerce and port-centric logistics. In addition, it was found that large warehouses have been increasingly taken up by retailers and manufacturers rather than logistics companies. Research impact: This paper examines the possible influence of economic and supply chain trends on warehousing in Great Britain. As well as testing existing theories, the data provides a sound foundation for future research. For example, there have been conflicting evidence in previous research regarding economies and diseconomies of scale and this discussion can now be set against trends in warehouse footprint and height. Practical impact: The paper provides a better understanding and basis for decision making by planners, developers, funding corporations, operators and end users. For example, topics such as size and height of buildings are examined, as well as trends in port-centric logistics, rail connections and e-fulfilment. The changing nature of warehouse designs in terms of wider economic and supply chain trends is particularly important for practitioners as warehousing costs are to a large extent determined at the design phase and have a major impact on the effectiveness of the overall supply chain of which they are a part.